Kontekst historyczny i kultura pamięci oraz ich znaczenie dla edukacji porównawczej - Nowakowska-Siuta, Renata (Studia Edukacyjne, 2022)
The article presents a new approach to comparative education in the Polish comparative discourse, based primarily on the ideas of pedagogical constructivism, opening a discussion on a new method- ological paradigm, which is the place of historical context and memory in comparative research. In Polish comparative education there is a tendency to attach less importance to the role of history and memory for a comprehensive grasp of the meaning of the phenomena analyzed and the search for answers to important cognitive problems. The traditional approach is focused on the present and fu- ture perspective and this is how educational problems are perceived in the discourse of comparative education. Taking into account the importance of historical thinking in the methodology of compara- tive education is important insofar as it shows a wide context and helps understand rather than only present phenomena. The contextual analysis, including the embedding of phenomena in their logic of historical events, is the basic task of comparative education.